'Sir Arthur Hirtzel and the Pax Britannica in the Middle East'. Issue 2 (3rd April 2021) - Fisher, John
ABSTRACT: Sir Arthur Hirtzel, the long-serving senior official in the India Office was an old – and a much respected – Middle Eastern hand. Few in Whitehall could rival him in his capacity 'to get into the mind of the man at the other end of the line.' Surprisingly, perhaps, Hirtzel never visited the region and never set foot in India, with which he was so intimately connected in an official capacity. As this examination of his role during the First World War and its immediate aftermath shows, Hirtzel's perspicacity concerning key political and military developments, as well as the opportunities and the constraints presented by the war, was striking. Notable was his percipience in predicting the import of Wilsonian idealism for Britain's ambitions in the wider Middle Eastern region. So too was his ability to adapt policy to the changing international environment. He also foresaw the considerable difficulties, especially financial pressures, which would arise in Iraq and affect British control there.